Strategi Pengembangan Usaha Dalam Meningkatkan Minat Konsumen Di Toko Amanda Jaya Kota Gorontalo - Irmawati Adam; Kurniadi K. Hasan; Sabriana Oktaviana Gintulangi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze business development strategies to increase consumer interest at Toko Amanda Jaya in Gorontalo City. The research method used is qualitative descriptive through observation, interviews, and documentation. The results of the study indicate that the utilization of social media is still minimal, business management is not well-structured, and human resource skills in digital marketing are limited, resulting in decreased consumer attraction. From a management perspective, business operations still rely heavily on the owner, and task allocation among employees is unclear. Meanwhile, in terms of basic operations, skills in digital marketing and customer service still need improvement. Therefore, it is necessary to optimize the use of social media consistently, implement more professional management in business governance, and enhance human resource capacity through training. By applying these strategies, Toko Amanda Jaya is expected to increase consumer interest, strengthen competitiveness, and be able to adapt to the developments of the modern market.